Synthesis of Oligosaccharides Derived from Lactulose (OsLu) Using Soluble and Immobilized Aspergillus oryzae β-Galactosidase - Cardelle-Cobas, Alejandra; Olano, Agustin; Irazoqui, Gabriela; Giacomini, Cecilia; Batista-Viera, Francisco; Corzo, Nieves; Corzo-Martínez, Marta (Frontiers in Bioengineering and Biotechnology, 2016)
b-galactosidase from Aspergillus oryzae offers a high yield for the synthesis of oligosaccharides derived from lactulose (OsLu) by transgalactosylation. Oligosaccharides with degree of polymerization (DP) ≥ 3 have shown to possess higher in vitro bifidogenic effect than di- and tetrasaccharides. Thus, in this work, an optimization of reaction conditions affecting the specific selectivity of A. oryzae b-galactosidase for synthesis of OsLu has been carried out to enhance OsLu with DP ≥ 3 production. Assays with b-galactosidase immobilized onto a glutaraldehyde-agarose support were also carried out with the aim of making the process cost-effective and industrially viable. Optimal conditions with both soluble and immobilized enzyme for the synthesis of OsLu with DP ≥ 3 were 50 °C, pH 6.5, 450 g/L of lactulose and 8 U/mL of enzyme, reaching yields of ca. 50% (w/v) of total OsLu and ca. 20% (w/v) of OsLu-3, being 6′-galactosyl-lactulose the major one, after a short reaction time. Selective formation of disaccharides, however, was favored at 60 °C, pH 4.5, 450 g/L of lactulose and 8 U/mL of enzyme. Immobilization increased the enzymatic stability to temperature changes and allowed to reuse the enzyme. We can conclude that the use, under determined optimal conditions, of the A. oryzae b-galactosidase immobilized on a support of glutaraldehyde-agarose constitutes an efficient and cost-effective alternative to the use of soluble b-galactosidases for the synthesis of prebiotic OsLu mixtures.